Accelerated partial breast irradiation using sole interstitial multicatheter brachytherapy compared with whole-breast irradiation with boost for early breast cancer: 10-year results of a GEC-ESTRO randomised, phase 3, non-inferiority trial. Issue 3 (March 2023) - Strnad, Vratislav; Polgár, Csaba; Ott, Oliver J; Hildebrandt, Guido; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Łyczek, Jarosław; Guinot, Jose Luis; Gutierrez Miguelez, Cristina; Slampa, Pavel; Allgäuer, Michael; et al.
Summary: Background: Several randomised, phase 3 trials have investigated the value of different techniques of accelerated partial breast irradiation (APBI) for patients with early breast cancer after breast-conserving surgery compared with whole-breast irradiation. In a phase 3 randomised trial, we evaluated whether APBI using multicatheter brachytherapy is non-inferior compared with whole-breast irradiation. Here, we present the 10-year follow-up results. Methods: We did a randomised, phase 3, non-inferiority trial at 16 hospitals and medical centres in Austria, Czech Republic, Germany, Hungary, Poland, Spain, and Switzerland. Patients aged 40 years or older with early invasive breast cancer or ductal carcinoma in situ treated with breast-conserving surgery were centrally randomly assigned (1:1) to receive either whole-breast irradiation or APBI using multicatheter brachytherapy. Whole-breast irradiation was delivered in 25 daily fractions of 50 Gy over 5 weeks, with a supplemental boost of 10 Gy to the tumour bed, and APBI was delivered as 30·1 Gy (seven fractions) and 32·0 Gy (eight fractions) of high-dose-rate brachytherapy in 5 days or as 50 Gy of pulsed-dose-rate brachytherapy over 5 treatment days. Neither patients nor investigators were masked to treatment allocation. The primary endpoint was ipsilateral local recurrence, analysed in the as-treated population; the non-inferiority margin for the recurrence rate difference (defined for 5-year results) was 3 percentage points. The trial is registered with ClinicalTrials.gov, NCT00402519 ; the trial is complete. Findings: Between April 20, 2004, and July 30, 2009, 1328 female patients were randomly assigned to whole breast irradiation (n=673) or APBI (n=655), of whom 551 in the whole-breast irradiation group and 633 in the APBI group were eligible for analysis. At a median follow-up of 10·36 years (IQR 9·12–11·28), the 10-year local recurrence rates were 1·58% (95% CI 0·37 to 2·8) in the whole-breast irradiation group and 3·51% (1·99 to 5·03) in the APBI group. The difference in 10-year rates between the groups was 1·93% (95% CI –0·018 to 3·87; p=0·074). Adverse events were mostly grade 1 and 2, in 234 (60%) of 393 participants in the whole-breast irradiation group and 314 (67%) of 470 participants in the APBI group, at 7·5-year or 10-year follow-up, or both. Patients in the APBI group had a significantly lower incidence of treatment-related grade 3 late side-effects than those in the whole-breast irradiation group (17 [4%] of 393 for whole-breast irradiation vs seven [1%] of 470 for APBI; p=0·021; at 7·5-year or 10-year follow-up, or both). At 10 years, the most common type of grade 3 adverse event in both treatment groups was fibrosis (six [2%] of 313 patients for whole-breast irradiation and three [1%] of 375 patients for APBI, p=0·56). No grade 4 adverse events or treatment-related deaths have been observed. Interpretation: Postoperative APBI using multicatheter brachytherapy after breast-conserving surgery in patients with early breast cancer is a valuable alternative to whole-breast irradiation in terms of treatment efficacy and is associated with fewer late side-effects. Funding: German Cancer Aid, Germany.